Are innovative firms more circular when women hold upper positions? - Saudi-Yulieth Enciso-Alfaro; Isabel-María García-Sánchez (Journal of Innovation & Knowledge (JIK), 2024)
The circular economy paradigm demands immediate and significant adjustments and changes in management and production business processes to maintain adequate to good ecosystem conditions for the use and development of human life. In this context, we analysed the impact of female leadership in the business environment and its relationship with the conservation of planetary health. This empowers women in the transition toward circular business model within the planet's capacity. For a panel data sample of the world's largest companies, we find that active female participation in high business positions leads to significant changes toward a model that protects the natural and endemic wealth of different ecosystems around de world. Additionally, we found that the active presence of women in the decision-making process concerning the protection of the environment, human development, and economic prosperity is strongly associated with the prospective knowledge that female independent directors possess, and to a greater extent, with the knowledge spillover that the presence of female executive directors entails.
Keywords: M14; O57; Q01; Q54; 650; Board gender diversity; Women directors; Circular economy; Ecological transition; Spillover effect; Knowledge; Sustainability